Dosis de ceniza en el rendimiento del rebrote del forraje Pennisetum sp. cuba 22. Iquitos, Perú - Guzman Ordoñez, Mijail (2024)
The use of ash as fertilizer in crops is not new, this work tries to show how much ash we need for greater forage production in humid tropics like the city of Iquitos. The Faculty of Agronomy of the National University of the Peruvian Amazon presents the present research work titled ASH DOSE IN THE PERFORMANCE OF FORAGE REGROWING Pennisetum sp. CUBA 22. IQUITOS, PERU. With a completely randomized block design with five treatments and four repetitions, where the treatments are T0 (control), T1 (100 kilos of ash/ha), T2 ((200 kilos of ash/ha), T3 (300 kilos of ash/ha) and T4 (400 kilos of ash/ha), obtaining the following results that the forage of Pennisetum sp. “Cuba 22” reacts positively to the increase in the doses of ash to the soil, it is suggested to use it for fertilization of forage Cuba 22 the T4 treatment (400 kilos of ash/ha) under our agroclimatic conditions of Zungarococha With regard to the variables of the agronomic characteristics of the study such as height of 1.74 meters, green matter of 5.08 kg/m2. of leaves of 2.03 kg/m2, of stems of 3.05 kg/m2 and dry matter of 1.02 kg/m2. This was achieved with the T4 treatment (400 kilos of ash/ha). The yield of green matter was 50,800 kilos per hectare. of aerial biomass with the T4 treatment (400 kilos of ash/ha).